The development of domestic space in the Maltese Islands from the late Middle Ages to the second half of the twentieth century - Said-Zammit, George A., (Archaeopress, 2016)
This study traces and analyses the evolution of domestic space in Maltese vernacular and 'polite' houses from medieval to contemporary times. The houses under review range from humble buildings of modest size, materials, and design, like farmhouses or those for the less affluent towndwellers, to buildings of grand design, like townhouses and palazzi.